25 ans de lutte pour l'unite antiimperialiste des étudiants et pour une université democratique (Union Internationale des Étudiants)
Grid of black and white photographs of student events promoted by the IUS; large raised fist in brown in the foreground Poster advertising 25th anniversary of the International Union of Students PO-1909